Internal Corrosion Rate Of Api 5l X-42 Steel In Crude Oil Production Installation Pipe - Septe.S, Edi (Pt. Anagata Sembagi Education, 2024)
Steel pipes remain the preferred choice for distribution and crude oil installation pipes in the oil and gas industry due to their strength, surface hardness, and cost-effectiveness. However, their susceptibility to corrosion in harsh environments poses significant challenges. This research focuses on analyzing the corrosion rate of API 5L X-42 steel in a crude oil environment at a temperature of 40°C. The corrosion rate was determined using the weight loss method, revealing that the rate varies over time. The findings of this study provide crucial insights for the industry, particularly in preventing leaks in crude oil installation pipes caused by corrosion. By understanding the corrosion behavior of steel pipes under specific conditions, the oil and gas industry can implement more effective maintenance strategies and material selection, ultimately enhancing the safety and longevity of pipeline infrastructure. The study highlights the importance of regular monitoring and the adoption of preventive measures to mitigate corrosion-related issues, thereby ensuring the continuous and safe operation of oil and gas installations